Crystallography and Its Impact on Carbonic Anhydrase Research. (13th September 2018) - Lomelino, Carrie L.; Andring, Jacob T.; McKenna, Robert
Abstract : X-ray and neutron crystallography are powerful techniques utilized to study the structures of biomolecules. Visualization of enzymes in complex with substrate/product and the capture of intermediate states can be related to activity to facilitate understanding of the catalytic mechanism. Subsequent analysis of small molecule binding within the enzyme active site provides insight into mechanisms of inhibition, supporting the design of novel inhibitors using a structure-guided approach. The first X-ray crystal structures were determined for small, ubiquitous enzymes such as carbonic anhydrase (CA). CAs are a family of zinc metalloenzymes that catalyze the hydration of CO2, producingH C O 3 - and a proton. The CA structure and ping-pong mechanism have been extensively studied and are well understood. Though the function of CA plays an important role in a variety of physiological functions, CA has also been associated with diseases such as glaucoma, edema, epilepsy, obesity, and cancer and is therefore recognized as a drug target. In this review, a brief history of crystallography and its impact on CA research is discussed.